New Wild Fields: How the Russian War Leads to the Demodernization of Ukraine's Occupied Territories - Маляренко, Тетяна Анатоліївна; Маляренко, Т. А.; Maliarenko, Tetiana A.; Malyarenko, Tetyana; Кормич, Борис Анатолійович; Кормич, Б. А.; Kormych, Borys A. (Cambridge : Cambridge University Press, 2024)
This article explores Russian occupation policy in Ukraine as an adaptive tactic of Russia’s grand strategy and a manifestation of its military culture. Based on a comparative analysis of the Russian occupation policy during the hybrid and conventional stages of the Russian-Ukrainian war, including the employment of a de facto state playbook, we find both continuity and shifts in Russia’s approach. Although the main shift lies in the change of Russia’s conflict management in neighboring countries from reactive to proactive, the main continuities are the subordination of occupation policy to Russia’s geostrategic interests and path dependence in its military culture, which together lead to the employment of brutal violence against civilians and the demodernization of occupied territories.
Malyarenko T. New Wild Fields: How the Russian War Leads to the Demodernization of Ukraine's Occupied Territories / T. Malyarenko, B. Kormych // Nationalities Papers. – Cambridge : Cambridge University Press, 2024. – 52(3). – P. 497–515. URL: https://doi.org/10.1017/nps.2023.33
Keywords: Occupation; policy; entrenchment; de facto states; demodernization; armed conflict; Ukraine; Russia